2008
DOI: 10.1002/art.23966
|View full text |Cite
|
Sign up to set email alerts
|

Mature antigen‐experienced T helper cells synthesize and secrete the B cell chemoattractant CXCL13 in the inflammatory environment of the rheumatoid joint

Abstract: Objective. Synovial B cells play a critical role in rheumatoid arthritis (RA), being involved in autoantibody synthesis, T cell activation, and cytokine production. CXCL13 is a B cell chemoattractant that is instrumental in synovial B cell organization; the regulatory determinants of CXCL13 in inflammation are poorly characterized. This study was undertaken to investigate the functional involvement of synovial T cells in the ectopic expression of CXCL13 in RA.Methods. CXCL13 production and regulation were addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
120
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(128 citation statements)
references
References 33 publications
8
120
0
Order By: Relevance
“…CXCL13 is a homeostatic B cell chemoattractant ( 43 ) that is required for the normal organization of B cell follicles in secondary lymphoid organs ( 44 ) and for recruiting B cells in extralymphoid sites when overexpressed ( 45 ). CXCL13 mRNA and protein expression and spontaneous CXCL13 secretion were detected in RA synovial fl uid T cells ( 46 ), and it was suggested that CXCL13 tissue expression may be critically involved in the process of ectopic lymphoid neogenesis, a phenomenon seen in 25-50% of RA patients, via recruitment of B cells into the synovium ( 47 ). TREM-1 is an immunoglobulinlike cell surface receptor mainly expressed on neutrophils and CD14 monocytes ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL13 is a homeostatic B cell chemoattractant ( 43 ) that is required for the normal organization of B cell follicles in secondary lymphoid organs ( 44 ) and for recruiting B cells in extralymphoid sites when overexpressed ( 45 ). CXCL13 mRNA and protein expression and spontaneous CXCL13 secretion were detected in RA synovial fl uid T cells ( 46 ), and it was suggested that CXCL13 tissue expression may be critically involved in the process of ectopic lymphoid neogenesis, a phenomenon seen in 25-50% of RA patients, via recruitment of B cells into the synovium ( 47 ). TREM-1 is an immunoglobulinlike cell surface receptor mainly expressed on neutrophils and CD14 monocytes ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…CXCR5 -CXCL13 + CD4 + T cells have also been detected in rheumatoid synovitis from patients but were not viewed as T FH cells because of their CXCR5 negativity (26,27).…”
Section: Cd3 + Cd4mentioning
confidence: 99%
“…14,15 It is also important that the effects of exercise are verified on immune cells involved in the pathophysiology of RA, for example in LY and macrophages (MF). 16 18 Thus, the effects of exercise on the function of these cells can be investigated through the quantification of their glucose and glutamine metabolism.…”
Section: Introductionmentioning
confidence: 99%